Work Inequalities in the Crisis Evidence from Europe - Vaughan-Whitehead, Daniel (Edward Elgar Publishing, 2011)
Work Inequalities in the Crisis provides an in-depth overview of the effects of the crisis on inequalities in the world of work. It examines these inequalities multi-dimensionally, looking at employment, wages and incomes, working conditions and social dialogue. At the same time, it investigates whether the crisis may halt the progress made in Europe towards better quality jobs and working conditions. This book offers a unique combination of research, case studies and policy discussions. An assessment of national trends in 30 European countries precedes case studies of 14 of them, in which noted European specialists report on individual enterprises or sectors. The volume's survey of national- and local-level policy solutions contributes to identifying those responses that strengthen economic competitiveness, preserve social cohesion and do not deepen inequalities. This timely resource will be of particular interest to academics, students and researchers in labour economics, to policymakers, and to those involved in European studies more generally.